Social imaginaries: the construction of reality and the “Politics of things” - Pintos de Cea-Naharro, Juan Luis; Torres Cubeiro, Manuel (Imagonautas, 2022)
The article describes a theoretical approach to both the methodology and the concept of social imaginaries built with the systemic constructive theory. The basic presumptions of this theory are first explained (1). Then, they are outlined within a sociological discussion about “reality” (2). At the same time, a precise concept of social imaginaries would be elaborated (3). Finally, the paper concludes with a brief discussion of the methodology of observation used in this approach and its consequences within the space of politics (4).